Children with medical complexity: A concept analysis. Issue 3 (24th February 2021) - Rogers, Jayne; Reed, Mary P.; Blaine, Kevin; Manning, Haylee
Abstract: Aim: The aim of this paper is to conduct a concept analysis on the term, "children with medical complexity." Background: Children with medical complexity (CMC) describes pediatric patients with chronic, sustained acuity; however, there is a lack of consensus in the literature regarding its exact meaning, characteristics, and implications. Design: This analysis relied upon the framework described by Walker and Avant. Data Source: The CINAHL, MEDLINE, and PubMed databases were queried from April 2020 to December 2020 with an initial search of the literature for the keyword, "children with medical complexity" and other associated terms, such as "pediatric medical complexity" and "nursing care of children with medical complexity." Review Methods: This analysis will explore the concept of CMC and its significance, attributes, antecedents, and consequences. Results: This investigation revealed that CMC are a growing population of pediatric patients who have one or more complex chronic conditions that affect multiple body systems, experience functional limitations, require extensive care coordination from multiple providers, and are dependent upon life‐sustaining medical technology. Conclusions: The findings can serve as a foundation for future work advancing the understanding of the topic of CMC.